2021
DOI: 10.2147/ott.s281011
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0067835 Knockdown Enhances the Radiosensitivity of Colorectal Cancer by miR-296-5p/IGF1R Axis

Abstract: Background: Colorectal cancer (CRC) is one of the most common malignant cancers globally. Circular RNAs (circRNAs) have been implicated in the development of CRC. In this paper, we set to explore the precise action of circ_0067835 in CRC progression and radioresistance. Methods: Quantitative real-time polymerase chain reaction (qRT-PCR) was used to evaluate the expression of circ_0067835, microRNA-296-5p (miR-296-5p) and insulin-like growth factor 1 receptor (IGF1R). Western blot was used to measure the level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 26 publications
(28 reference statements)
0
35
0
Order By: Relevance
“…Furthermore, exosomal circ_IFT80 desensitizes recipient cells to radiation [42]. In their studies, circ_0067835 and circ_IFT80 were found to positively regulate the level of insulin-like growth factor 1 receptor (IGF1R) and musashi-1 (MSI1), respectively, by sponging miR-296-5p [37,42] (Figure 2 and Table 1). IGF1R and MSI1 have been investigated to reduce radiosensitivity by activating DNA damage repair [56,57].…”
Section: Circ_0067835 and Circ_ift80mentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, exosomal circ_IFT80 desensitizes recipient cells to radiation [42]. In their studies, circ_0067835 and circ_IFT80 were found to positively regulate the level of insulin-like growth factor 1 receptor (IGF1R) and musashi-1 (MSI1), respectively, by sponging miR-296-5p [37,42] (Figure 2 and Table 1). IGF1R and MSI1 have been investigated to reduce radiosensitivity by activating DNA damage repair [56,57].…”
Section: Circ_0067835 and Circ_ift80mentioning
confidence: 95%
“…Circ_0067835 is abundant in blood-derived exosomes from patients who received radiotherapy, suggesting an involvement of this circRNA in radiosensitivity modulation. Indeed, it was noticed that radiotherapy-induced apoptosis is increased in cancer cells treated with exosomes derived from circ_0067835-silenced cells [37]. Furthermore, exosomal circ_IFT80 desensitizes recipient cells to radiation [42].…”
Section: Circ_0067835 and Circ_ift80mentioning
confidence: 99%
“…Wang et al, 2021 [ 222 ] explained the role of hsa_circ_0067835 in the suppression of CRC cell radiosensitivity by miR-296-5p/IGF1R axis.…”
Section: Oncogenic Functions Of Circrnasmentioning
confidence: 99%
“…Moreover, it was shown that hsa-circRNA-0067835 (circIFT80) gene knockout can enhance the radiosensitivity of CRC through the miR-296-5p/IGF1R axis. 8 CircIFT80 also promotes the progression of CRC through the miR-1236-3p/ HOXB7 axis. 9 In summary, it shows that circIFT80 plays an important role in the tumor progression of CRC.…”
Section: Introductionmentioning
confidence: 99%